Notas sobre carófitos de Costa Rica. II - Gómez P., Luis Diego (1971)
Two species of Nitella are reported from Costa Rica for the first time and briefly described, following those included in a previous papero A key for the determination of the species of Charophyta from Costa Rica and Central America, as known today, is included. At present, seven species of Charophytes are known from Costa Rica.